LOCAL CONTENT REGULATIONS IN INFRASTRUCTURE DEVELOPMENT AND THE NATIONAL TREATMENT PRINCIPLE - Suhendra, Hartono; Amalia, Prita (Transnational Business Law Journal, 2024)
The local content requirement is a policy aimed at promoting domestic industries and reducing dependence on imported products. However, its application, particularly in the procurement of goods for solar power plants, raises concerns about potential violations of the national treatment principle found in international agreements such as GATT 1994 and the Agreement on TRIMs. This study seeks to explore the implementation of local content requirements in infrastructure project procurement in relation to the national treatment principle and the government's efforts to enforce these regulations. The research employs a normative juridical approach, drawing on literature sources and analyzing the issue based on legal principles. The study is descriptive-analytical in nature, utilizing secondary data gathered from primary, secondary, and tertiary legal materials through literature review and analyzed using qualitative juridical methods. The findings indicate that the application of local content requirements in the procurement of infrastructure projects for solar power plants in Indonesia is not fully aligned with the national treatment principle. The government has made efforts to enforce local content requirements without breaching international law by implementing incentives and providing exceptions for imported goods under certain conditions.